Key tips to shift student perspectives through transformative learning in medical education - Efraim J. Hart; Merel H. de Heer-Koster; Maria van der Harst; Joyce L. Browne; Fedde Scheele (BMC Medical Education)
Abstract Healthcare systems are increasingly complex, facing challenges such as rising costs, aging populations, and persistent health inequities. These challenges demand that medical education adapts, to equip health professionals with the competencies required to navigate and transform complex systems. This is where transformative learning theory can play a crucial role. This article offers twelve practical tips to integrate transformative learning in medical education, emphasizing the need for a shift from traditional educational approaches to more transformative methods. These tips focus on educating learners on the principles of transformative learning, encouraging critical reflection, fostering interdisciplinary collaboration, addressing the hidden curriculum, and creating a supportive learning environment. By implementing these tips, medical education can better prepare healthcare professionals to act as change agents, contributing to the long-term sustainability and effectiveness of healthcare systems. The potential impact of these tips on medical education is substantial, as they provide a pathway toward a more responsive, ethical, and sustainable future of healthcare. Clinical trial number: Not applicable.